ANALISIS PERKEMBANGAN DAN TANTANGAN PERBANKAN SYARIAH DI KUWAIT - Asnawi Asnawi; Hikmah Indri Yani Harahap; Risa Lidia; Khaidar Rahmaini Jamila (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Islamic banking is a vital component of the global Islamic financial system, particularly in the Gulf Cooperation Council (GCC) region. Kuwait is known as a pioneer in the development of Islamic banking through the establishment of Kuwait Finance House (KFH) in 1977. This study aims to analyze the development of Islamic banking in Kuwait, encompassing its history, profiles of major Islamic banks, products and operational mechanisms, and challenges faced. The research method used was qualitative research with a library research approach. Data was collected from books, scientific journals, official reports, and other relevant documents, then analyzed using content analysis techniques. The results indicate that Islamic banking in Kuwait has experienced significant growth thanks to regulatory support from the Central Bank of Kuwait (CBK) and product innovation based on Sharia principles. However, the industry still faces challenges such as limited human resources, Sharia compliance risks, and the potential for fraud that can impact public trust.